2008
DOI: 10.1073/pnas.0712073105
|View full text |Cite
|
Sign up to set email alerts
|

In vitro reconstitution and crystal structure of p -aminobenzoate N -oxygenase (AurF) involved in aureothin biosynthesis

Abstract: p-aminobenzoate N-oxygenase (AurF) from Streptomyces thioluteus catalyzes the formation of unusual polyketide synthase starter unit p-nitrobenzoic acid (pNBA) from p-aminobenzoic acid (pABA) in the biosynthesis of antibiotic aureothin. AurF is a metalloenzyme, but its native enzymatic activity has not been demonstrated in vitro, and its catalytic mechanism is unclear. In addition, the nature of the cofactor remains a controversy. Here, we report the in vitro reconstitution of the AurF enzyme activity, the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
216
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(223 citation statements)
references
References 35 publications
5
216
2
Order By: Relevance
“…By measuring whole-cell activities of Streptomyces lividans containing genes for wild-type and deletion variants of the aureothin pathway on expression plasmids, AurF was proposed to sequentially oxidize p-aminobenzoate to p-nitrobenzoate (66,206). AurF was independently purified and characterized, showing that p-hydroxylaminobenzoate and p-nitrosobenzoate are intermediates of the reaction (28). Analysis of crystal structures, combined with previous biochemical spectroscopy studies, confirmed that AurF contains two iron atoms in the active site (28,176).…”
Section: Naturally Occurring Nitroaromatic Compoundsmentioning
confidence: 88%
See 1 more Smart Citation
“…By measuring whole-cell activities of Streptomyces lividans containing genes for wild-type and deletion variants of the aureothin pathway on expression plasmids, AurF was proposed to sequentially oxidize p-aminobenzoate to p-nitrobenzoate (66,206). AurF was independently purified and characterized, showing that p-hydroxylaminobenzoate and p-nitrosobenzoate are intermediates of the reaction (28). Analysis of crystal structures, combined with previous biochemical spectroscopy studies, confirmed that AurF contains two iron atoms in the active site (28,176).…”
Section: Naturally Occurring Nitroaromatic Compoundsmentioning
confidence: 88%
“…AurF was independently purified and characterized, showing that p-hydroxylaminobenzoate and p-nitrosobenzoate are intermediates of the reaction (28). Analysis of crystal structures, combined with previous biochemical spectroscopy studies, confirmed that AurF contains two iron atoms in the active site (28,176). The only other characterized homologs of AurF are NorF from Streptomyces orinoci HKI-0260 and SpnF from Streptomyces spectabilis, which are responsible for the biosynthesis of orinocin in S. orinoci (195) and of neoaureothin (spectinabilin) in S. spectabilis (27), respectively.…”
Section: Naturally Occurring Nitroaromatic Compoundsmentioning
confidence: 99%
“…There have been conflicting reports regarding the structure of AurF, some suggesting the active site contains diiron while others suggesting an iron and manganese complex (Krebs et al, 2007;Zocher et al, 2007). While some structural and biochemical data suggest that AurF may employ a binuclear manganese center, Choi et al (2008) indicated that a diiron center is more likely in the Streptomyces thioluteus AurF. In contrast, PrnD is a Rieske mononuclear non-heme enzyme that catalyzes the oxidation of the amino group of aminopyrrolnitrin to a nitro group, forming pyrrolnitrin.…”
Section: Us Army Engineermentioning
confidence: 94%
“…An inspection of a protein alignment amongst the three proteins revealed that the characteristic iron binding EX28-33DEX2H motif (Krebs et al, 2007) is present in RHAIro06104. Analysis of the crystal structure of the AurF protein (PDB ID: 3CHH_B) from S. thioluteus (Choi et al, 2008) indicates that the amino acids in this binding motif at positions 200-202 are closely associated with the diiron center. The residues believed to comprise the active site pocket showed amino acid substitutions that were conserved based on similar side chain chemistries (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation